2005
DOI: 10.1007/s11172-005-0217-4
|View full text |Cite
|
Sign up to set email alerts
|

Structure of acetyl chloride molecule isotopomers CH3COCl and CD3COCl in the ground and lowest excited singlet and triplet electronic states: a quantum mechanical study

Abstract: The structures of isotopomers of conformationally flexible acetyl chloride molecule, CH 3 COCl and CD 3 COCl, in the ground (S 0 ) and lowest excited singlet (S 1 ) and triplet (T 1 ) electronic states were calculated by the RHF, MP2, and CASSCF methods. The equilibrium geometric parameters and harmonic vibrational frequencies of the molecules in these elec tronic states were estimated. According to calculations, electronic excitation causes consider able conformational changes involving rotation of the CH 3 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…The “ V 6 ” value has been estimated to be −0.019 kcal/mol. The negative sign of “ V 6 ” for the AC molecule is in accordance with that reported by Kudich et al, where the values of “ V 6 ” had been predicted to vary between −10.5 and −11.4 cm –1 , depending upon the level of theories computed over different basis sets. In this connection, it is also worth to mention that for the acetaldehyde molecule, the sign of the corresponding “ V 6 ” term is also negative for fully relaxed optimizations, signifying strong coupling of methyl torsion with the out-of-plane γ (C aldehyde –H) wagging motion of the molecule.…”
Section: Results and Discussionsupporting
confidence: 91%
“…The “ V 6 ” value has been estimated to be −0.019 kcal/mol. The negative sign of “ V 6 ” for the AC molecule is in accordance with that reported by Kudich et al, where the values of “ V 6 ” had been predicted to vary between −10.5 and −11.4 cm –1 , depending upon the level of theories computed over different basis sets. In this connection, it is also worth to mention that for the acetaldehyde molecule, the sign of the corresponding “ V 6 ” term is also negative for fully relaxed optimizations, signifying strong coupling of methyl torsion with the out-of-plane γ (C aldehyde –H) wagging motion of the molecule.…”
Section: Results and Discussionsupporting
confidence: 91%
“…Sumathi and Chandra optimized the geometries of CH 3 COCl and CH 3 CO at the MP2 level of theory with the 6-31G(d) and 6-31lG(d,p) basis sets 22a. In addition, energy barrier for CH 3 CO dissociation is predicted to be 19.1 kcal/mol at the MP2/cc-pVTZ level by Deshmukh et al The structures of CH 3 COCl in the S 1 and T 1 electronic states were calculated by the MP2 and CASSCF methods . It was found that electronic excitation causes considerable conformational changes involving rotation of the CH 3 top and a substantial deviation of the CCOCl fragment from planarity.…”
Section: Introductionmentioning
confidence: 99%